Non-cardiac surgery in patients with coronary stents: the RECO study. Issue 19 (26th July 2011) - Albaladejo, Pierre; Marret, Emmanuel; Samama, Charles-Marc; Collet, Jean-Philippe; Abhay, Kou; Loutrel, Olivier; Charbonneau, Hélène; Jaber, Samir; Thoret, Sophie; Bosson, Jean-Luc; Piriou, Vincent
Abstract : Context: Interruption or maintenance of oral antiplatelet therapy (OAT) during an invasive procedure may result in ischaemic and/or haemorrhagic complications. There is currently a lack of clear guidance regarding the issue of treatment interruption during surgical procedures. Objective: To evaluate the rate of major adverse cardiac and cerebrovascular events (MACCEs) and major or minor bleeding complications and their associated independent correlates in coronary stented patients undergoing urgent or planned non-cardiac surgery. Design, setting, and patients: Prospective, multicentre, observational cohort study of 1134 consecutive patients with coronary stents. Main outcome measures: The co-primary endpoints consisted of the incidence of MACCE and major bleeding within the first 30 days of an invasive procedure. Results: MACCE and haemorrhagic complications were observed in 124 (10.9%) and 108 (9.5%) patients, respectively, within an average time delay from invasive procedure to event of 3.3±3.9 and 5.3±5.3 days. Independent preoperative correlates for MACCE were complete OAT interruption for more than 5 days prior to surgery, preoperative haemoglobin <10 g/dl, creatinine clearance of <30 ml/min and emergency or high-risk surgery. Independent factors for haemorrhagic complications were preoperative haemoglobin <10 g/dl, creatinine clearance between 30 and 60 ml/min, a delay from stent implantation to surgery <3 months and high-risk surgery according to the Lee classification. Conclusions: Patients with coronary stents undergoing an invasive procedure are at high risk of perioperative myocardial infarction including stent thrombosis irrespective of the stent type and major bleeding. Interruption of OAT more than 5 days prior to an invasive procedure is a key player for MACCE. Clinical Trial Registration: NCT01045850.